SELF-EFFICACY OF JUNIOR HIGH SCHOOL STUDENTS IN MATHEMATIC PROBLEM SOLVING - Siregar, Rama Nida; Prabawanto, Sufyani; Suryadi, Didi (SIGMA DIDAKTIKA: Jurnal Pendidikan Matematika, 2021)
This study aims to describe the self-efficacy of junior high school students in Medan City and Deli Serdang Regency, North Sumatra in solving mathematical problems in social arithmetic material. This research includes survey research with quantitative and qualitative approaches. The research subjects were 67 junior high school students in Medan City and Deli Serdang Regency, North Sumatra who came from two schools with the category of one public school and one private school. The instrument used is a self-efficacy questionnaire consisting of 27 statement items based on self-efficacy indicators that will be filled out by students, and interview guidelines. The results showed that the average self-efficacy of private junior high school students in Medan City and Deli Serdang Regency, North Sumatra as a whole of 67 students was in the high category, which was 90.24. In general, students have a high tendency of self-efficacy. For example, having confidence or confidence in the abilities possessed in carrying out and completing the tasks at hand so that they are able to overcome obstacles and achieve the expected goals, so it can be concluded that students who have high efficacy abilities will have an impact on their learning achievement and students' mathematical problem solving. getting better.